AI-Enabled Market Access: Farmers’ Perspectives on Digital Platforms and Their Impact on Agricultural Trade in Remote Areas - Denta Rahma Fitriyani; Muhammad Nasir (Politeknik Siber Cerdika Internasional, 2025)
The rapid expansion of digital platforms has created new opportunities for farmers in remote areas to access larger markets, yet significant challenges remain. This study investigates the accessibility, economic implications, and trust issues associated with digital platform adoption among farmers in rural regions. The research aims to explore how these platforms impact agricultural trade by addressing key factors influencing usability, financial viability, and security concerns. A qualitative approach was employed, focusing on in-depth interviews and focus groups with small-scale farmers who engage in digital transactions. Findings indicate that while digital platforms improve pricing transparency and provide market opportunities, challenges such as high transaction fees, logistics costs, and limited digital literacy inhibit their full potential. Trust issues, including data security and payment reliability, further affect adoption rates, underscoring the importance of user-centered design and affordable access models. Practical implications suggest the need for digital literacy programs, simplified interfaces, and enhanced security features tailored to the unique needs of rural farmers. This research highlights critical areas for intervention, aiming to make digital platforms more inclusive and economically viable for the agricultural sector in remote areas.